36x-96-15x-15+140-20x=80-20x-48x-30

Simple and best practice solution for 36x-96-15x-15+140-20x=80-20x-48x-30 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36x-96-15x-15+140-20x=80-20x-48x-30 equation:


Simplifying
36x + -96 + -15x + -15 + 140 + -20x = 80 + -20x + -48x + -30

Reorder the terms:
-96 + -15 + 140 + 36x + -15x + -20x = 80 + -20x + -48x + -30

Combine like terms: -96 + -15 = -111
-111 + 140 + 36x + -15x + -20x = 80 + -20x + -48x + -30

Combine like terms: -111 + 140 = 29
29 + 36x + -15x + -20x = 80 + -20x + -48x + -30

Combine like terms: 36x + -15x = 21x
29 + 21x + -20x = 80 + -20x + -48x + -30

Combine like terms: 21x + -20x = 1x
29 + 1x = 80 + -20x + -48x + -30

Reorder the terms:
29 + 1x = 80 + -30 + -20x + -48x

Combine like terms: 80 + -30 = 50
29 + 1x = 50 + -20x + -48x

Combine like terms: -20x + -48x = -68x
29 + 1x = 50 + -68x

Solving
29 + 1x = 50 + -68x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '68x' to each side of the equation.
29 + 1x + 68x = 50 + -68x + 68x

Combine like terms: 1x + 68x = 69x
29 + 69x = 50 + -68x + 68x

Combine like terms: -68x + 68x = 0
29 + 69x = 50 + 0
29 + 69x = 50

Add '-29' to each side of the equation.
29 + -29 + 69x = 50 + -29

Combine like terms: 29 + -29 = 0
0 + 69x = 50 + -29
69x = 50 + -29

Combine like terms: 50 + -29 = 21
69x = 21

Divide each side by '69'.
x = 0.3043478261

Simplifying
x = 0.3043478261

See similar equations:

| 8+2w+w^2= | | 3n^2-16n+12=0 | | sin^2(2x)-3sin(2x)+1=0 | | 3(16-18)/2(10) | | (2v+1)(4+v)=0 | | .4(x+2)=1.4(x+1.5) | | 72x-120-1-32x-16+12x+36=30x-1 | | -4(t-7)-(t+4)=7 | | (4x+12)=0 | | x^2+rx-s=0 | | 4(x-3)-7=3(x+2)+6x | | -8y+6x+9=0 | | 2(1+x)=(25825000) | | 230=-5(6p-4) | | 7i+6=-6 | | 11x-3y=54 | | 9+7(x-6)=3-2(x-9) | | P=4c-(20+c) | | 2x+2=2x+4 | | y=4x^2-20x+25 | | (1.1+4.7)x=22.5 | | x=.666x+2 | | 8b^4-b^3-b^4+4b^3-4= | | x+53=x | | 0.2-2x=-1.4 | | (x^-5/9y^1/2/x^-2/9)^-6 | | 2(x-10)+7=27x+1 | | 1/6z^-6 | | 7k^2=-2+15k | | (5b-8)(5b+3)=25b^2-25b-24 | | -5x+3x=-5 | | 7k^2-15k-2=0 |

Equations solver categories